Enhancing Ad hoc Networks Performance by Using Location and Energy Information (University of Khartoum Engineering Journal, 2022)
Mobile ad hoc network (MANET) is considered to be a promising technology for the near future. This calls for more efficient mechanisms and methods to fulfil the expectation of end users and at the same time make the best use of resources. Although of its variety of applications and potentials, MANET has issues such as resource limitation, routing overhead and changing of wireless link. This paper proposes three algorithms that can diminish the overhead and energy consumption of MANET and at the same time improve the overall performance of the network. By Controlling the Route Request (RREQ) broadcasting in the Ad-hoc On-Demand Distance Vector (AODV) routing protocol using location and energy information, a better resource management and hence a better performance for the overall network is achieved.